Comparative effectiveness of ultrasound guided intratendinous prolotherapy injection with conventional treatment to treat focal supraspinatus tendinosis : randomised control study - George, J.; Chn'g, L.S.; Jaafar, Z.; Hamid, M.S.A. (2014)

(untitled)
Even though supraspinatus tendinosis is a common problem, there is not much literature on treatment of supraspinator tendinosis with direct tendon injectables compared to other tendinosis such as lateral epicondylitis.